2002
DOI: 10.1152/japplphysiol.00473.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transient mechanical benefits of a deep inflation in the injured mouse lung

Abstract: Allen, Gilman, Lennart K. A. Lundblad, Polly Parsons, and Jason H. T. Bates. Transient mechanical benefits of a deep inflation in the injured mouse lung. J Appl Physiol 93: 1709-1715. First published July 12, 2002 10.1152/japplphysiol.00473.2002The lasting effects of a recruitment maneuver (RM) in the injured lung are not well characterized. We speculated that the reduction in respiratory elastance (H) after a deep inflation (DI) is transient in nature and should be sustained longer at higher positive end-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 37 publications
3
41
0
1
Order By: Relevance
“…Infrequent application of large RMs had transient effects on H; however the pattern of progressive increase in H after the IM followed a similar trajectory to that seen before the IM. This finding is in line with those from other studies in animals with healthy and pre-injured lungs (Mead and Collier, 1959;Allen et al, 2002;Allen et al, 2004;Frank et al, 2005;Allen et al, 2006;Ko et al, 2008) and may reflect inadequate PEEP during low V T ventilation.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Infrequent application of large RMs had transient effects on H; however the pattern of progressive increase in H after the IM followed a similar trajectory to that seen before the IM. This finding is in line with those from other studies in animals with healthy and pre-injured lungs (Mead and Collier, 1959;Allen et al, 2002;Allen et al, 2004;Frank et al, 2005;Allen et al, 2006;Ko et al, 2008) and may reflect inadequate PEEP during low V T ventilation.…”
supporting
confidence: 92%
“…It is essential to provide information on ventilator settings in order to facilitate future studies. However, apart from specific "recruitment maneuver studies" (Allen et al, 2002;Allen et al, 2004;Frank et al, 2005;Koh et al, 2005;Farias et al, 2005;Allen et al, 2006;Allen et al, 2007;Ko et al, 2008;Jonasson et al, 2008) few experimental studies using mechanical ventilation protocols provide detailed information on application, frequency, and type of lung volume recruitment maneuvers (RMs). Given that the mechanical properties of the respiratory system are specific to the lung volume at which their measurements are made (Sly et al, 2003) and to the lung volume history , it is surprising that details of RMs are not always reported.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue elastance began to rise after 1 h and reached significantly elevated levels at 2-4 h of MV (P<0.05, Figure 2). These changes were accompanied by a decrease in static compliance over the same period of time ( Figure 2) and were consistent with the effects of MV observed in other studies utilizing low ventilation volumes (29,30). By comparison, central airway resistance and lung tissue damping did not change over time.…”
Section: Induces Pulmonary Inflammation Accompanied By Changes In supporting
confidence: 89%
“…15,26 Part of the confusion surrounding the use of recruitment maneuvers in ALI may stem from the underappreciated fact that recruitment and derecruitment in the lung are dynamic processes that evolve with time, 10 even in the face of a perfectly constant ventilatory regimen. Furthermore, several studies in mice from our laboratory [3][4][5][6] have shown that the dynamics of recruitment and derecruitment depend markedly on the nature and severity of lung injury, likely reflecting variations in the degree of instability of the liquid layer that lines the small airways.…”
Section: Introductionmentioning
confidence: 99%